1995
DOI: 10.1177/000348949510400911
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis as a Prognostic Marker in Early Head and Neck Cancer

Abstract: Experimental evidence suggests that tumor growth beyond the earliest stages is dependent on angiogenesis, or neovascularization, and that angiogenesis may also promote metastasis. Recent clinical studies demonstrate that angiogenesis is a prognostic marker in breast, lung, and prostate cancer. To investigate whether tumor angiogenesis also correlates with metastasis and survival in early head and neck carcinoma, we quantified the microvascularity of 106 primary carcinomas prior to treatment and correlated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 12 publications
3
56
2
Order By: Relevance
“…In this study, tumor vascularity was not predictive of the response of a tumor to chemoradiotherapy [40]. Tumor angiogenesis has shown to positively correlate with nodal metastasis in carcinoma of the tongue floor of mouth and nasopharynx [41][42][43][44][45][46]. However, tumor microvessel density has been reported to not serve as a predictor of lymph node metastasis by several authors examining tumors from various sites in the head and neck.…”
Section: Angiogenesismentioning
confidence: 55%
“…In this study, tumor vascularity was not predictive of the response of a tumor to chemoradiotherapy [40]. Tumor angiogenesis has shown to positively correlate with nodal metastasis in carcinoma of the tongue floor of mouth and nasopharynx [41][42][43][44][45][46]. However, tumor microvessel density has been reported to not serve as a predictor of lymph node metastasis by several authors examining tumors from various sites in the head and neck.…”
Section: Angiogenesismentioning
confidence: 55%
“…For squamous cells carcinomas of the head and neck, as for other tumour types such as carcinoma of the breast, conflicting results have been reported. Some investigators found a correlation between vascular density and metastatic potential (Gasparini et al, 1993;Albo et al, 1994;Shpitzer et al, 1996;Murray et al, 1997), whereas others did not (Leedy et al, 1994;Dray et al, 1995;ZĂ€tterström et al, 1995;Janot et al, 1996;Moriyama et al, 1997;Salven et al, 1997;Burian et al, 1999). In this study no correlation was found between vascular density and N-stage, even when the 75th percentile value or the highest value of the subareas were used.…”
Section: Vascular Parametersmentioning
confidence: 99%
“…Single parameters such as polarographic pO 2 measurements and microvascular density have been demonstrated to be prognostic indicators in a variety of tumour types, including carcinomas of the head and neck (Gatenby et al, 1987;Dray et al, 1995;ZĂ€tterström et al, 1995;Jenssen et al, 1996;Nordsmark et al, 1996;Brizel et al, 1997). However, considering the complexity of the micro-environmental system, it is unlikely that a single parameter can reliably predict treatment outcome on an individual basis.…”
mentioning
confidence: 99%
“…3,4 In head and neck squamous cell carcinoma, the quantification of tumor angiogenesis by intratumoral microvessel counting correlates with poor clinical outcome, 5,6 but results of various studies are conflicting and inconclusive in regard of the size of the estimated risk. 7,8 A number of putative angiogenic factors such as basic fibroblast growth factor, platelet-derived growth factor, interleukins, and vascular endothelial growth factor (VEGF), are expressed in head and neck squamous cell carcinoma. 4 VEGF is considered a leading candidate for tumor angiogenesis in head and neck squamous cell carcinoma, exhibiting its effect in the vasculature in a paracrine pattern.…”
mentioning
confidence: 99%